VITALITAS SEKUJANG DI KABUPATEN SELUMA - Sarwo Ferdi Wibowo (Balai Bahasa Kalimantan Barat, 2020)
Previous research resume Sekujang almost vanish not based on suitable indicators. This research aim to make previous finding more measurable by using modified language vitality indicators to measure folklore vitality. The same way applied by Pusat Perlindungan Badan Bahasa in 2017. This research used mix method through questionnaire to collect quantitative data and interview to elaborate collected quantitative data. Result shows Sekujang nowadays categorized as eroding folklore (total score 0,42) with main threaten factors 1) not adaptive to ecranitation, 2) unintegrated to local content curriculum, 3) occlusion of intergeneration transmission. The reflection of this research exposed theoretical laxity on basic assumption by using language vitality indicators that is 1) language death not always followed by folklore; 2) quite impossible to determine folklore authenticity benchmark because always reproduce and recreate in it transmission process.